2022
DOI: 10.3390/v14030512
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Phage Infecting the Marine Photoheterotrophic Bacterium Citromicrobium bathyomarinum

Abstract: This study isolated and characterized a new phage infecting the marine photoheterotrophic bacterium Citromicrobium bathyomarinum, which fills the gap in research on phages targeting this ecologically important species. The phage vB_CbaS-RXM (RXM) has a dsDNA genome with a length of 104,206 bp and G+C content of 61.64%. The taxonomic analysis found a close evolutionary relationship between RXM, Erythrobacter phage vB_EliS-L02, and Sphingobium phage Lacusarx, and we propose that RXM represents a new species of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Every 10 min, subsamples were collected, and the viral abundance was detected using the double-layer agar method. The burst size was calculated as the ratio between the number of virions at the growth plateau and the initial number of infected host cells [54].…”
Section: Methodsmentioning
confidence: 99%
“…Every 10 min, subsamples were collected, and the viral abundance was detected using the double-layer agar method. The burst size was calculated as the ratio between the number of virions at the growth plateau and the initial number of infected host cells [54].…”
Section: Methodsmentioning
confidence: 99%
“…Here, we established a systematic CbK‐like collection with a total of 30 members (Table 1), including the CbK‐like phage vB_CbaS‐RXM that we recently reported (Ma et al, 2022) and six CbK‐like sequences (including prophage genomes) that we identified from different proteobacterial genomes. To predict the capacity of these phages for lysogeny, the phage recombinase and attP – attB pairing were systematically analysed, and both culture‐dependent and culture‐independent lysogeny tests were conducted.…”
Section: Introductionmentioning
confidence: 99%